2019
DOI: 10.1186/s40248-019-0194-3
|View full text |Cite
|
Sign up to set email alerts
|

Indoor exposure to particulate matter and volatile organic compounds in dwellings and workplaces and respiratory health in French farmers

Abstract: IntroductionFew investigations have related objective assessments of indoor air pollutants to respiratory health in farmers, in spite of the many rural environmental hazards to which they are exposed. Chemical air pollution has been particularly neglected.ObjectiveWe investigated the relationships of indoor exposure to particulate matter (PM) and volatile organic compounds (VOCs) to respiratory health in farmers.MethodsNineteen VOCs (5 families) and PM (from ultrafine to total suspended particles (TSP)) were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Urinary VOC metabolites have a half-life in the order of days, which is longer than that of blood VOCs which is only of hours. Urinary VOC metabolites also indicate VOC exposure from indoor and outdoor sources and are a better indicator of internal dose than environmental indoor VOCs measurement [ 41 , 42 , 43 , 44 ]. Exposure measures were performed by laboratories of the National Center of Environmental Health (NCEH) of the CDC with rigorous methods and several covariates were adjusted for in our analysis to minimize residual confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary VOC metabolites have a half-life in the order of days, which is longer than that of blood VOCs which is only of hours. Urinary VOC metabolites also indicate VOC exposure from indoor and outdoor sources and are a better indicator of internal dose than environmental indoor VOCs measurement [ 41 , 42 , 43 , 44 ]. Exposure measures were performed by laboratories of the National Center of Environmental Health (NCEH) of the CDC with rigorous methods and several covariates were adjusted for in our analysis to minimize residual confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation types and the plant composition of green spaces vary across the globe, resulting in different types and amounts of VOCs. Some plant VOCs decrease lung function and increase the risk of COPD [87,88]. Second, higher greenspace exposure increased the pollen concentration.…”
Section: Impact Pathwaysmentioning
confidence: 99%
“…Benzene is a known carcinogen categorized under Group-1 as per IARC, responsible for causing leukemia, multiple myeloma, and lung, liver, and biliary tract cancer. Being genotoxic in nature affects the bone marrow cells, causing chromosomal abnormality, while the association with aplastic anemia and respiratory effects, including asthma, are also observed (Maesano et al, 2019;Dantas et al, 2022). Toluene exposure causes dizziness, nausea, CNS depression, paresthesia, cerebellar ataxia or incoordination, renal toxicity, neurological disorders, vision disruption, and color vision loss, while maternal-effect includes premature delivery, delay in post-natal development, ); while some of the studies have been reported in India measuring the impact of covid-19 lockdown on air quality but for a very short term period (Chauhan and Singh, 2020; Jain and Sharma, 2020; Kotnala et al, 2020 Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%